Green IT : managing your carbon footprint. (British Informatics Society Ltd., 2012)
New legislation, rising energy costs and increasing demand for green credentials have moved sustainable IT up the business agenda. This ebook looks at different aspects of green IT - from sustainably managing IT assets, ethically recycling hardware or using IT to reduce carbon footprint - and how to incorporate them in business strategy.